Stress Response of Siniperca chuatsi to Transport Stimuli Using Compound Feed and Live Bait - Yuanliang Duan; Qiang Li; Zhipeng Huang; Zhongmeng Zhao; Han Zhao; Yang Feng; Senyue Liu; Chengyan Mou; Jian Zhou; Lu Zhang (Animals)
The transition from live bait (LF) feeding to compound feed (CF) feeding in aquaculture is of great production significance. In recent decades, cultivation with CF has become a focus for practitioners and researchers dealing with Siniperca chuatsi. This study focused on experimental subjects of S. chuatsi fed with CF and LF, using short-distance transportation as a stimulating factor. For the first time, the differences between S. chuatsi fed with CF and LF were analyzed from the perspective of stress response during transportation. This study found that after transportation stimulation, the activities of LZM and the contents of MDA, TGs, and glucose in the brain, liver, kidneys, muscles, stomach, pyloric caecum, intestines, and blood of S. chuatsi fed with CF were higher compared to S. chuatsi fed with LF (p < 0.05). Significant differences were observed in the impacts of various diets on the gastrointestinal tract, particularly in the intestine. In summary, this study found that S. chuatsi fed with CF could retain more energy after transport stimulation and exhibited stronger resistance to microbial stress, but they had a weaker antioxidant capacity. Therefore, in future research on CF for S. chuatsi, we need to focus on its ability to enhance antioxidant capacity.